Posterior Spinal Artery Aneurysm Presenting with Leukocytoclastic Vasculitis - Hill, Travis C. (J Cerebrovasc Endovasc Neurosurg, 2016)
Rupture of isolated posterior spinal artery (PSA) aneurysms is a rare cause of subarachnoid hemorrhage (SAH) that presents unique diagnostic challenges owing to a nuanced clinical presentation. Here, we report on the diagnosis and management of the first known case of an isolated PSA aneurysm in the context of leukocytoclastic vasculitis. A 53-year-old male presented to an outside institution with acute bilateral lower extremity paralysis 9 days after admission for recurrent cellulitis. Early magnetic resonance imaging was read as negative and repeat imaging 15 days after presentation revealed SAH and a compressive spinal subdural hematoma. Angiography identified a PSA aneurysm at T9, as well as other areas suspicious for inflammatory or post-hemorrhagic reactive changes. The patient underwent a multilevel laminectomy for clot evacuation and aneurysm resection to prevent future hemorrhage and to establish a diagnosis. The postoperative course was complicated by medical issues and led to the diagnosis of leukocytoclastic vasculitis that may have predisposed the patient to aneurysm development. Literature review reveals greater mortality for cervical lesions than thoracolumbar lesions and that the presence of meningitic symptoms portents better functional outcome than symptoms of cord compression. The outcome obtained in this case is consistent with outcomes reported in the literature.